Phospho-mTOR in non-tumour and tumour bladder urothelium: Pattern of expression and impact on urothelial bladder cancer patients - Afonso, Julieta (2014)
Urothelial bladder carcinoma (UBC) is heterogeneous in its pathology and clinical behaviour. Evaluation of prognostic and predictive biomarkers is necessary, in order to produce personalised treatment options. The present study used immunohistochemistry to evaluate UBC sections containing tumour and non-tumour areas from 76 patients, for the detection of p-mTOR, CD31 and D2-40 (blood and lymphatic vessels identification, respectively). Of the non-tumour and tumour sections, 36 and 20% were scored positive for p-mTOR expression, respectively. Immunoexpression was observed in umbrella cells from non-tumour urothelium, in all cell layers from non-muscle-invasive (NMI) tumours (including expression in superficial cells), and in spots of cells from muscle-invasive (MI) tumours. Positive expression decreased from non-tumour to tumour urothelium, and from pTl/pTis to pT3/pT4 tumours; however, the few pT3/pT4 positive cases had worse survival rates, with 5-year disease-free survival being significantly lower. Angiogenesis occurrence was impaired in pT3/pT4 tumours that did not express p-mTOR. In conclusion, p-mTOR expression in non-tumour umbrella cells is likely a reflection of their metabolic plasticity, and extension to the inner layers of the urothelium in NMI tumours is consistent with an enhanced malignant potential. The expression in cell spots in a few MI tumours and absence of expression in the remaining tumours is intriguing and requires further research. Additional studies regarding the up- and downstream effectors of the mTOR pathway should be conducted.